Becoming Experts in Their Own Treatment: Child and Caregiver Engagement With Burn Scar Treatments. (May 2023) - Killey, Jessica; Simons, Megan; Prescott, Sarah; Kimble, Roy; Tyack, Zephanie
Children who experience a severe burn injury not only require acute medical care but may also need ongoing rehabilitation. To mitigate the potential long-term consequences of scarring and the impact of scarring on their everyday lives, children may be expected to use a variety of time-consuming and multi-component non-invasive scar treatments (such as pressure garments and silicone gels). These treatments may pose unique challenges for children and their caregivers. With limited research previously addressing how Australian children navigate the use of scar treatments at home, this study aimed to develop a grounded theory of children and their caregivers' engagement with non-invasive burn scar treatments. Using a constructivist grounded theory approach, interviews were completed with 20 caregivers and 7 children, and a theory of children and their caregivers becoming experts in the use of non-invasive burn scar treatments was developed. Through persistence and flexibility, they continued to develop expertise. Engaging with scar treatments was an evolving process over time for children with burns and their caregivers. Theoretical categories identified included 'making it work', 'finding the balance' and 'seeking reassurance' and highlighted the remarkable strengths and adaptability of children and their caregivers. Through trial and error, children and their caregivers developed their own unique strategies for engaging with scar treatments. These insightful results may inform the development of interventions to support children and their caregivers' day-to-day engagement with non-invasive burn scar treatments and guide health professionals recommending these treatments.